DEVELOPING PROBLEM-BASED LEARNING MODEL BASED ON BAKIAK GAME FOR LEARNING MATHEMATICS AT ELEMENTARY SCHOOLS - Nur Imama; Sri Utaminingsih; Hilal Madjdi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to develop a Problem Based Learning (PBL) model based on the traditional game “Bakiak” for mathematics learning at elementary schools. This study employed Research and Development (R&D) methods using the Borg and Gall model, which was simplified into eight steps: (1) potential and problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing, (7) product revision, and (8) trial use. The subjects of this study were fifth-grade elementary school students from several schools in Kabupaten Pati. The results of the study produced a PBL model based on the “Bakiak” game for mathematics learning at the elementary school level on the topics of speed, distance, and time for grade V. In the guiding phase, individual and group investigations were integrated with the “Bakiak” game. The syntax for developing the model consisted of seven stages, namely student orientation to problems, organizing students to learn, guiding individual and group investigations, assisting in data analysis, helping students discover mathematical concepts, developing work results, and analyzing and evaluating the learning process. The product and research instruments were validated by media experts, material experts, and learning experts, obtaining a score of 3.47 in the very good category. Therefore, the development of a PBL model based on the “Bakiak” game was feasible for use in mathematics learning.